Islamic Social Reporting Disclosure of Sharia Commercial Banks in Indonesia: A Form of Social Responsibility - Riduwan Riduwan; Rofiul Wahyudi; Lu’liyatul Mutmainah (Shirkah: Journal of Economics and Business, 2020)
Sharia industry development encourages experts to design Corporate Social Responsibility (CSR) disclosure index that is more compatible with the characteristics of sharia-based corporate. However, studies examining CSR disclosure using Islamic Social Reporting (ISR) index that focuses on detailed results of content analysis from time to time still remains a paucity of evidence. Hence, this study aims to examine the practice of Islamic Social Reporting disclosure of sharia commercial banks in Indonesia. Drawing on the data obtained from CSR reports established by sharia banks in Indonesia, the results of content analysis disclosed that the ISR disclosure showed a fluctuating trend. It was also revealed that the six themes of ISR index have not been optimally disclosed. ISR disclosures of sharia banks in Indonesia were categorized as good since the average disclosure reached 50% in 2015 up to 2017, especially the corporate governance disclosure. This study’s results imply that it is necessary to increase the disclosures that can be strengthened by regulations from financial regulators and Islamic banking associations to increase public trust and value-added of sharia commercial banks. This study contributes to the development of sharia banks as fruitful insights on policy recommendations for Islamic banks' top management.